Rosemary and CoQ10 Alleviated the Detrimental Effects of Concomitant Administration of Acetaminophen and Carbamazepine by Accelerating Their Metabolism and Elimination - Marwa Magdy Hamido; Nashwah Ismail Zaki; Sawsan Ahmed Nasr; Wael Mohamed El-Sayed (The Indonesian Biomedical Journal, 2022)
BACKGROUND: The interaction of carbamazepine (CBZ) and acetaminophen (APAP) could result in hepatic failure and mortality. This study was conducted to analyzed the potential of rosemary ethanol extract (REE) or coenzyme Q10 (CoQ10) to alleviate the interactions between CBZ and APAP.METHODS: Fourty-eight adult male rats were treated differently based on the assigned groups. Oxidative stress parameters, including malondialdehyde (MDA), glutathione (GSH), glutathione peroxidase (GPx), superoxide dismutase (SOD), catalase, and glutathione S-transferase (GST), and the expression levels of CYP3A4, CYP2E1, IL-6, TNF-α, and IL-1B in the liver were estimated. In addition, the histopathology of liver was examined and the plasma clearance rate of CBZ and APAP was estimated.RESULTS: Combination of CBZ and APAP significantly elevated alanine aminotransferase (ALT) activity and hepatic MDA, and reduced the activities of GPx, GST, and GSH level in liver. The gene expression of CYP3A4 and CYP2E1 was upregulated by CBZ and CoQ10, respectively. The expression of IL-6 has decreased in the groups treated with CBZ alone or in combination with APAP. TNF-α expression was significantly downregulated in the groups treated with CBZ, APAP, REE, CoQ10, or combination CBZ and APAP. The liver from CBZ and APAP combination group showed centrolobular degeneration and necrosis. REE and CoQ10 were able to alleviate most of these detrimental effects. The combined administration of CBZ and APAP extended the plasma clearance time of APAP and CBZ from 6 to 24 and from 9 to 24 hours, respectively.CONCLUSION: REE and CoQ10 alleviated the detrimental effects of the combination of CBZ and APAP through enhancing the cellular antioxidant milieu, induction of metabolizing enzymes, reduction of the plasma half-life of APAP and CBZ preventing their accumulation and potential interaction.KEYWORDS: acetaminophen, antioxidants, carbamazepine, CoQ10, CYP3A4, CYP2E1, glutathione, lipid peroxidation, rosemary